ATTITUDE TOWARDS ONLINE RETAILING SERVICES: A COMPARISON OF STUDENT AND NON-STUDENT SAMPLES - Siohong Tih; Sean Ennis; June M. L. Poon (Asian Academy of Management Journal, 2008)
This study examined the adequacy of using undergraduate student samples in research on online consumer attitudes by comparing the attitudes of students (n = 161) towards online retailing services with the attitudes of non-students (n = 252) towards such services. A structured questionnaire administered online was used to gather data on perceptions, satisfaction, and behavioral intentions with regard to online retailing services. The t-test results showed that, in general, students' attitude towards online retailing services is similar to that of non-students. Therefore, undergraduate students may be reasonable surrogates for consumers in research on online retailing.